THE EFFECT OF ROA, ROE, AND EPS ON STOCK PRICES OF COMPANIES REGISTERED ON JII FOR THE 2018-2021 - Putri, Ema Santika; Usdeldi, Usdeldi; Rahma, Sri (Al Dzahab, 2024)
Purpose: This study aims to analyse the effect of Return On Assets, Return on Equity, and Earnings Per Share on stock prices in companies listed on JII for 2018-2021. Desain/Methodology/Approach: The authors use quantitative research to obtain data by accessing the company's financial statements. The samples used in this study were 12 companies registered on JII for the 2014-2018 period, passing through the purposive sampling stage according to the criteria needed for the study. The data analysis method used in this study is panel data regression techniques. Findings: The research results show that Return On Assets (ROA) has an effect on stock prices in a positive direction, Return on Equity (ROE) has an effect on stock prices in a negative direction, and Earning Per Share (EPS) affects stock prices in a negative direction. ROA, ROE, and EPS affect stock prices at 96.44%, while other variables outside the research explain the remaining 3.56%. Research Implications: Inform investors or potential investors about the importance of analysing the company's financial statements before investing.